Professional Training and Digital Competence in Teaching: A Systematic Review of the Literature - Yonathan Humberto Borden Lanza; Beatriz Lores Gómez; Mireia Usart Rodríguez (Revista Latinoamericana de Tecnología Educativa, 2025)
This research aims to analyse the scientific evidence regarding the levels of Digital Competence (DC) among Vocational Education and Training (VET) teachers in Spain. To achieve this, a systematic review of the literature is presented as a research design, following the PRISMA-P Statement. The databases consulted were Dialnet, Scopus, and Web of Science, covering the search period from 2014 to 2022. Following the filtering process, 12 studies were selected for further analysis. The results indicate that in the past decade, there has been a notable increase in research aimed at recognising and examining the levels of Digital Competence in Teaching (DCT), as well as its impact on teaching-learning processes. However, there exists a scarcity of published scientific output. It has been concluded that teachers, in general, and Vocational Training teachers, in particular, perceive themselves to be at a low level of development in digital teaching competence. It is essential to implement research instruments that assist them in: (1) identifying their actual level of Digital Teaching Competence, and (2) providing training proposals that enhance the areas constituting Digital Teaching Competence and shape their attitudes towards the use of Digital Technologies.